Respuesta :
I think you are saying 3b^2 - b so if b = 5 first you should solve the exponent, so
3 * 5^2 - 5
3 * 25 - 5
then you just solve the rest normally
3 * 25 - 5
75 - 5
70
and you should get 70
3 * 5^2 - 5
3 * 25 - 5
then you just solve the rest normally
3 * 25 - 5
75 - 5
70
and you should get 70
The value of the expression 3b² - b when b = 5 is 70
From the question, the given expression is 3b2−b.
This can be written properly as 3b² - b.
Now to determine the value of 3b² - b when b = 5. That means, we should substitute the value 5 for b in the given expression.
Now, putting b = 5 in the expression, we get
[tex]3b^{2}-b = 3(5)^{2}-5[/tex]
[tex]= 3 \times (5)^{2} - 5[/tex]
Then,
[tex]3b^{2}-b = 3 \times 25-5[/tex]
(NOTE: [tex]5^{2} = 5 \times 5 = 25[/tex])
∴ [tex]3b^{2}-b = 75-5[/tex]
(NOTE: Multiplication(M) comes before subtraction (S) in BODMAS, so you multiply before subtracting)
∴ [tex]3b^{2}-b = 70[/tex]
Therefore the value of the expression 3b² - b when b = 5 is 70
Hence, the value of the expression 3b² - b when b = 5 is 70
Learn more here: https://brainly.com/question/2697710